A cross-sectional study of opinion about mental illness among undergraduate medical students with and without exposure to the psychiatry clinical rotation/postings during their undergraduate training - B. Neeraj Raj; B. K. Shivakumar; H. R. Vinay (Indian Journal of Psychiatry)
Background: A positive attitude toward mental illness is a prerequisite for the provision of holistic care. Thus, a study was undertaken to know the opinion about mental illness among medical students with and without exposure to the psychiatry clinical rotation/postings during their undergraduate training. Materials and Methods: This is a descriptive, cross-sectional study conducted at Adichunchanagiri Institute of Medical Sciences (AIMS), Karnataka. The sample comprised medical undergraduate students with and without exposure to psychiatry clinical postings, respectively. Self-administered socio-demographic and opinion about mental illness (OMI) questionnaires were used to collect the data. Result: Medical undergraduates from 1st and 2nd years who were unexposed to psychiatry and students from 3rd and 4th years who had exposure to psychiatry constituted about 52.17% (n = 252) and 47.83% (n = 231) of the overall sample size. A positive opinion toward mental illness was seen across various subsections of OMI questionnaire, especially in students who had attended psychiatry clinical posting. Conclusion: Opinions can change based on one’s experiences. A positive opinion toward mental illness was seen across medical undergraduate students who had completed psychiatry clinical postings in our study. The study provides valuable insights across various domains or areas wherein a teacher can focus and adjust the teaching methodologies accordingly. In the long run, it might have a positive influence on medical students to understand mental disorders, diagnose them, and manage patients with mental illness.